Handbook of Hydrocarbon and Lipid Microbiology - Timmis, Kenneth N.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
"Water is life!" All active cellular systems require water as the medium and solvent of their metabolic activities. Hydrophobic compounds and structures, which tend to exclude water, though providing inter alia excellent sources of energy and a means of biological compartmentalization, present problems of cellular handling, poor bioavailability and, in some cases, toxicity. Microbes both synthesize and exploit a vast range of hydrophobic organics, especially petroleum oil hydrocarbons and industrial pollutants, and the underlying interactions not only have major consequences for the lifestyles of the microbes involved, but also for biogeochemistry, climate change, environmental pollution, human health and a range of biotechnological applications. The aim of this handbook is to be the definitive resource of current knowledge on the diverse and multifaceted aspects of these interactions, the microbial players, and the physiological mechanisms and adaptive strategies characteristic of the microbial lifestyle that plays out at hydrophobic material: aqueous liquid interfaces.
Keywords: Life sciences; Microbiology; Biochemistry; Microbial ecology; Microbial genetics; Biotechnology; Life Sciences; Microbiology; Applied Microbiology; Environmental Engineering/Biotechnology.; Biochemistry, general; Microbial Ecology; Microbial Genetics and Genomics